Quantitative Detection of Respiratory Chlamydia pneumoniae Infection by Real-Time PCR - Kuoppa, Yvonne (American Society for Microbiology, 2002)
Real-time PCR was evaluated as a quantitative diagnostic method for Chlamydia pneumoniae infection using different respiratory samples. Real-time PCR had efficiency equal to or better than that of nested touchdown PCR. This study confirmed sputum as the best sampling material to detect an ongoing C. pneumoniae infection.